STEP-organizing a major project to tackle significant uncertainty - Methven, P (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2024)
This article describes why Spherical Tokamak for Energy Production (STEP) has been launched, what it aims to achieve (benefits) and, principally, how the whole programme will be delivered (strategy). The article draws on the work of major project delivery and organization design (OD) and applies this to the context of STEP, which is dominated by significant uncertainty in all dimensions (technical, financial, commercial and programmatic), where there is embryonic delivery capability, but where there are also global-scale opportunities. This leads to an approach based on securing and organizing the correct capability from both public and private sectors to work in a collaborative arrangement with a single purpose and, critically, in an operating model designed to manage uncertainty and emerging risks and to exploit opportunities. Placing adaptability at the core of the OD, particularly the ability to deliver emergent strategy through guided empowerment in pursuit of an ambitious aim, is a further development beyond much of the current thinking in major projects. The article concludes with an appendix that translates that programme approach into principles for managing the engineering design work.This article is part of the theme issue 'Delivering Fusion Energy - The Spherical Tokamak for Energy Production (STEP)'.